Discontinuous crack growth and toughening mechanisms in concrete: A numerical study based on the beam-particle approach. (15th February 2019) - Oliver-Leblond, C.
Highlights: Beam-particle approach to study mixed-mode fracture tests on cement mortar. Visualization and quantification of cracking through graph theory. Extensive use of image correlation to apply boundary conditions and compare numerical and experimental results. Abstract: In this paper, mixed-mode tests are studied using a beam-particle model adapted to the study of quasi-brittle cementitious materials. After a short presentation of the model, post-processing tools to visualize and quantify the cracks' propagation are described. A parametric study on a three-point bending test is then carried out in order to highlighté the model's ability to represent touéening mechanisms appearing during the softening phase. Finally, the mixed-mode tests of the CARPIUC benchmark are studied. These tests are particularly interesting because of their advanced use of image correlation. Indeed, monitoring is carried out during the tests to stably propagate the cracking along a complex path. In addition, the experimental displacements were post-processed on the boundaries to apply as boundary conditions for a numerical simulation. A comparison between numerical and experimental results shows the abilities of the beam-particle model.